Chinese Medicine Huzhen Tongfeng Formula Effectively Attenuates Gouty Arthritis by Inhibiting Arachidonic Acid Metabolism and Inflammatory Mediators - Jianping Deng; Zicong Wu; Chen Chen; Zhenling Zhao; Yifei Li; Zhengquan Su; Yiguang Lin; Yifei Wang; Zhiping Wang (Mediators of Inflammation)
The Chinese herbal medicine, Huzhen Tongfeng Formula (HZTF), derived from traditional Chinese medicine (TCM) practice, has recognized therapeutic benefits for gouty arthritis (GA). HZTF is currently in the late stage of approval process as a new anti-GA drug application. However, the underlying mechanism of HZTF as an antigout medication is unclear. In this study, we combined network pharmacology and experimental validation approaches to elucidate the mechanism of action of HZTF. First, the relative drug-disease target networks were constructed and analyzed for pathway enrichment. Potential pathways were then validated by in vitro and in vivo experiments. We found that 34 compounds from HZTF matched 181 potential drug targets. Topology analysis revealed 77 core targets of HZTF, which were highly related to gout, following screening of KEGG pathway enrichment. Further analysis demonstrated that the arachidonic acid metabolic pathway was the most relevant pathway involved in the mechanism of HZTF. Validation experiments showed that HZTF significantly inhibited the inflammatory cell infiltration into gouty joints, improved the swelling of affected joints, and increased the pain threshold. HZTF significantly reduced the transcription and production of various cytokines and inflammatory mediators in vitro. In particular, cyclooxygenase (COX)-1, COX-2, and 5-lipoxygenase were simultaneously downregulated. In conclusion, our study suggests that the antigout mechanism of HZTF is associated with the inhibition of the arachidonic acid pathway, resulting in the suppression of inflammatory cytokines and mediators. These findings extend our understanding of the pharmacological action of HZTF, rationalizing the application HZTF as an effective herbal therapy for GA.